Comprehensive Functional Analysis of Escherichia coli Ribosomal RNA Methyltransferases - Pletnev, Philipp; Guseva, Ekaterina; Zanina, Anna; Evfratov, Sergey; Dzama, Margarita; Treshin, Vsevolod; Pogorel’skaya, Alexandra; Osterman, Ilya; Golovina, Anna; Rubtsova, Maria; Serebryakova, Marina; Pobeguts, Olga V.; et al. (Frontiers in Genetics, 2020)
Ribosomal RNAs in all organisms are methylated. The functional role of the majority of modified nucleotides is unknown. We systematically questioned the influence of rRNA methylation in Escherichia coli on a number of characteristics of bacterial cells with the help of a set of rRNA methyltransferase (MT) gene knockout strains from the Keio collection. Analysis of ribosomal subunits sedimentation profiles of the knockout strains revealed a surprisingly small number of rRNA MT that significantly affected ribosome assembly. Accumulation of the assembly intermediates was observed only for the rlmE knockout strain whose growth was retarded most significantly among other rRNA MT knockout strains. Accumulation of the 17S rRNA precursor was observed for rsmA(ksgA) knockout cells as well as for cells devoid of functional rsmB and rlmC genes. Significant differences were found among the WT and the majority of rRNA MT knockout strains in their ability to sustain exogenous protein overexpression. While the majority of the rRNA MT knockout strains supported suboptimal reporter gene expression, the strain devoid of the rsmF gene demonstrated a moderate increase in the yield of ectopic gene expression. Comparative 2D protein gel analysis of rRNA MT knockout strains revealed only minor perturbations of the proteome.